1986
DOI: 10.1017/s0022172400062562
|View full text |Cite
|
Sign up to set email alerts
|

The detection ofChlamydia trachomatisby direct immunofluorescence in conjunctival smears from patients with trachoma and patients with ophthalmia neonatorum using a conjugated monoclonal antibody

Abstract: SUMMARYDuplicate specimens were taken with cotton-wool swabs from the upper tarsal conjunctiva of 63 patients living in Gambian villages in which trachoma is endemic and from 34 infants with ophthalmia neonatorum (ON) attending an outpatient clinic in The Gambia. The detection of Chlamydia trachomatis by direct immunofluorescence (IF) using a conjugated monoclonal antibody to its principal outer membrane protein was compared with isolation in cycloheximide-treated McCoy cells. For trachoma, the sensitivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…32 The sensitivity of a direct imunofluorescence screening test is variable with positivity rates as low as 8% for clinically active cases of trachoma. 33,34 In the present study, we observed that direct imunofluorescence was positive in 25% cases that were clinically positive for trachoma. The low positivity rate might prevent the use of direct imunofluorescence as a popular investigation for epidemiological studies in India because of cost considerations.…”
Section: Discussionsupporting
confidence: 58%
“…32 The sensitivity of a direct imunofluorescence screening test is variable with positivity rates as low as 8% for clinically active cases of trachoma. 33,34 In the present study, we observed that direct imunofluorescence was positive in 25% cases that were clinically positive for trachoma. The low positivity rate might prevent the use of direct imunofluorescence as a popular investigation for epidemiological studies in India because of cost considerations.…”
Section: Discussionsupporting
confidence: 58%
“…Microscopy requires trained technicians (224), is time-consuming, and is probably the least sensitive method for diagnosis (189). Additionally, collection of conjunctival scrapings with a metal blade is painful and unpopular (126). Tests that are less traumatic, more rapid, and more sensitive have displaced microscopy of scrapings to the sidelines of Chlamydia diagnostics.…”
Section: Microscopymentioning
confidence: 99%
“…A direct fluorescent antibody test, the Syva MicroTrak (Syva, Palo Alto, Calif.), was the first diagnostic reagent that used a monoclonal antibody against C. trachomatis and began the move away from culture to techniques that do not rely on chlamydial viability (M. E. Ward, 2002 For the clinician, specimen collection for the direct fluorescent antibody test is straightforward: conjunctival cells and exudates from a swab are smeared onto a slide in the field or clinic, fixed with methanol (189), and air dried. The slides are easy to transport and store (126). In the laboratory, the fixed sample is stained with fluorescein isothiocyanate-conjugated monoclonal antibody and examined under a fluorescence microscope.…”
Section: Direct Fluorescent Antibodymentioning
confidence: 99%
“…6 The argument against this method has been that the collection of conjunctival scrapings with a metal blade is painful and unpopular. 7 However this technique has since been replaced by superior techniques which are far more expensive and technically difficult to perform in remote areas. The use of conjunctival impression cytology-a noninvasive, painless, simple OPD procedure, which has met with good patient compliance-is a promising technique which needs to be evaluated further in community screening of trachoma.…”
Section: Discussionmentioning
confidence: 99%